STRATEGI BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI DESA SUMERTA KELOD KECAMATAN DENPASAR TIMUR, KOTA DENPASAR - Puspitawati, Ni Putu Sania; Purnamaningsih, Putu Eka; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022)
This BUMDES was formed on the legal basis of PP RI No. 11/2021 regarding BUMDES. This BUMDES has a trading unit, photocopy and ATK, PPOB, and a Parking Service Unit. However, in increasing PADes there are still some obstacles. Among them, the village government does not fully shop at BUMDes, lack of socialization, lack of coordination with several banjar clients, difficulty finding parking attendants, and weather and pandemics. This research use desciptive qualitative approach. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is SWOT analysis. The result of this research is that BUMDes seems quite able to identify its internal and external environment. BUMDes Dasa Kriya Loka Amerta in formulating strategies is still said to be not optimal. BUMDes Dasa Kriya Loka Amerta in implementing its strategy is quite good. And BUMDEs Dasa Kriya Loka Amerta have done a good evaluation. From these results, researchers provide alternative strategies in the form of opening business units and programs needed by the community, innovating, socializing, and receiving input and suggestions from the Village Government. Keywords: Strategy, Village Owned Enterprises (BUMDes), Village Original Income (PADes)